A Model of Medium Depolarisation Effects on Polarisation Vector Position - Hanuska, J.; Moc, J. (Radioengineering Society, 1994)
The paper presents the results of modelling the influence of real atmosphere with precipitation clouds on the radar signal polarisation status. The relationship between the signal vector depolarisation shift value and the initial wave polarisation is examined.
Keywords: electromagnetic wave propagation; depolarisation in atmosphere; polarisation vector; passive radar